1, 3-Oxazine as a chiral building block used in the total synthesis of (+)-1-deoxynojirimycin and (2R, 5R)-dihydroxymethyl-(3R, 4R)-dihydroxypyrrolidine. Issue 12 (15th July 2015) - Park, Seok-Hwi; Kim, Ji-Yeon; Kim, Jin-Seok; Jung, Changyoung; Song, Dong-Keun; Ham, Won-Hun
Graphical abstract: Abstract: Concise and stereocontrolled syntheses of (+)-1-deoxynojirimycin and (2 R, 5 R )-dihydroxymethyl-(3 R, 4 R )-dihydroxypyrrolidine [(+)-DMDP] were achieved via a diastereomerically enriched oxazine intermediate. The key strategies include the use of 1, 3-oxazine as a chiral building block and diastereoselective nucleophilic addition to an aldehyde. Starting from readily available ( R )-methyl 2-benzamido-3-(( tert -butyldimethylsilyl)oxy)propanoate, (+)-1-deoxynojirimycin was synthesized in 11 steps and 26.2% overall yield while (+)-DMDP was synthesized in 11 steps and 27.1% overall yield, respectively. Abstract : ( S )-1-((4 R, 5 R, 6 R )-5-(( tert -Butyldimethylsilyl)oxy)-4-((( tert -butyldimethylsilyl)oxy)methyl)-2-phenyl-5, 6-dihydro-4 H -1, 3-oxazin-6-yl)ethane-1, 2-diol: C25 H45 NO5 Si [ α ]D 25  = +21.5 ( c 1.0, CHCl3 ) Source of chirality:d -serine Absolute configuration: ( S )(4 R, 5 R, 6 R ) Abstract : (3 S, 4 R, 5 R, 6 R )-5-(( tert -Butyldimethylsilyl)oxy)-6-((( tert -butyldimethylsilyl)oxy)methyl)piperidine-3, 4-diol: C18 H41 NO4 Si [ α ]D 25  = +55.5 ( c 0.1, CHCl3 ) Source of chirality:d -serine Absolute configuration: (3 S, 4 R, 5 R, 6 R ) Abstract : (2 R, 3 R, 4 R, 5 S )-2-(Hydroxymethyl)piperidine-3, 4, 5-triol: C6 H13 NO4 [ α ]D 25  = +40.8 ( c 0.8, H2 O) Source of chirality:d -serine Absolute configuration: (2 R, 3 R, 4 R, 5 S ) Abstract : ( S )-1-((4 R, 5 R, 6 S )-5-(( tert -Butyldimethylsilyl)oxy)-4-((( tert -butyldimethylsilyl)oxy)methyl)-2-phenyl-5, 6-dihydro-4 H -1, 3-oxazin-6-yl)allyl methanesulfonate: C27 H47 NO6 SSi2 [ α ]D 25  = +11.2 ( c 0.47, CHCl3 ) Source of chirality:d -serine Absolute configuration: ( S )(4 R, 5 R, 6 S ) Abstract : (2 R, 3 R, 4 R, 5 R )-4-(( tert -Butyldimethylsilyl)oxy)-5-((( tert -butyldimethylsilyl)oxy)methyl)-2-(hydroxymethyl)pyrrolidin-3-ol: C18 H41 NO4 Si2 [ α ]D 25  = +11.6 ( c 0.5, CHCl3 ) Source of chirality:d -serine Absolute configuration: (2 R, 3 R, 4 R, 5 R ) Abstract : (2 R, 3 R, 4 R, 5 R )-2, 5-Bis(hydroxymethyl)pyrrolidine-3, 4-diol: C6 H13 NO4 [ α ]D 25  = +55.2 ( c 0.9, H2 O) Source of chirality:d -serine Absolute configuration: (2 R, 3 R, 4 R, 5 R )